(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2023)
References: metaphor-meaning-eeg. (2021, 02 24). Récupéré sur neurosciencenews.com/metaphor-meaning-eeg-10979/ Abrams, J., & Zweig, C. (1991). Meeting the Shadow: The Hidden Power of the Dark Side of Human Nature. Los Angeles: Jeremy P.Tarcher, INC. Adichie, C. N. (2013). Americanah. New York: Alfred A. Knopf. Bhabha, H. (1994). The Location of Culture. New York: Routledge. Brone, G., & Vandaele, J. (2009). Cognitive Poetics: Goals, Gains, and Gaps. Berlin: Walter de Gruyter GmbH & Co. Chika, U. (2012). On Black Sisters’ Street. New York: Random House. Chukwudi-Ofoedu, A. (2017). The Domination and Sexual Objectification of Women in Chika Unigwe’s On Black Sisters’ Street. Journal of Humanities and Social Policy, 1-9. Emmot, C. (2002). “Split selves” in fiction and in medical “life stories”: Cognitive linguistic theory and narrative practice. In E. Semino, & J. Culpeper, Cognitive Stylistics: Language and Cognition in Text Analysis (pp. 153-181). Philadelphia: John Benjamins Publishing Co. Fanon, F. (1963). The Wretched of the Earth. New York: Grove Press. Gomez, A. B. (2015). The DIVIDED SELF metaphor: A cognitive-linguistic study of two poems by Nabokov. International Journal of English Studies, 97-113. Grossman, B. (2017). Metaphorical Expressions of Self Awareness in English. ELR Journal, 82-105. Lakoff, G. (1987). Women, Fire, and Dangerous Things. Chicago: The University of Chicago Press. Lakoff, G. (1992). The Metaphorical Models of the Self Inherent in Our Conceptual System. The Conceptual Self in Context. Atlanta: UC Berkeley. Lakoff, G. (1996). Sorry I’m not myself today: The metaphor system for conceptualizing the Self. In G. Fauconnier, & E. Sweeter, Spaces, worlds, and grammar (pp. 91-123). Chicago: University of Chicago Press. Lakoff, G., & Johnson, M. (1999). Philosophy in the Flesh. New York: Basic Books. Okolo, I. G. (2019). Unsettled Subjects: Sex Work in Chika Unigwe’s On Black Sisters’ Street. English Studies in Africa, 112-123. Reinares, L. B. (2019). The Pedagogies of Sex Trafficking Postcolonial Fiction: Consent, Agency, and Neoliberalism in Chika Unigwe’s On Black Sisters’ Street. Canadian Review of Comparative Literature, 56-76. Stockwell, P. (2002). Cognitive Poetics: an introduction. London: Routledge.